TRANSFORMASI EKONOMI DIGITAL DI INDONESIA: PELUANG, TANTANGAN DAN STRATEGI PENGEMBANGAN - Sutisna, Uken; Anwarul Umam, Raihan; Morisson, Buci (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The transformation of the digital economy in Indonesia has become one of the main drivers of economic growth and social development. This process opens up various opportunities, but also faces complex challenges. This article aims to identify the opportunities and challenges that arise along with the development of the digital economy, as well as the development strategies that need to be implemented to support the acceleration of this transformation. Using a qualitative approach and literature study method, this research analyzes various relevant literature on the phenomenon of the digital economy in Indonesia, such as the current growth of the digital economy, development challenges, development opportunities, and strategies for strengthening the digital economy. The results show that although Indonesia has great potential to become a major player in the global digital economy, there are still significant barriers such as digital infrastructure gaps, limited skilled human resources, and regulations that are not yet fully supportive. Therefore, development strategies that can be implemented include improving the quality of technological infrastructure, developing digital skills among the workforce, and improving policies and regulations that support the digital ecosystem. With the right policies and support from various parties, the transformation of the digital economy in Indonesia is expected to contribute significantly to inclusive and sustainable economic growth. Keywords: transformation, digital economy, development strategy